2016
DOI: 10.1002/jssc.201600485
|View full text |Cite
|
Sign up to set email alerts
|

Application of a solid‐phase microextraction fiber coated with a graphene oxide‐poly(dimethylsiloxane) composite for the extraction of triazoles from water

Abstract: A solid-phase microextraction fiber was prepared by mixing graphene oxide and hydroxyl-terminated polydimethylsiloxane together and then coating the mixture on the surface of etched stainless-steel wire by sol-gel technology. After aging by heating, the graphene oxide-polydimethylsiloxane composite coated fiber was used for the direct solid phase microextraction of triazole fungicides from water samples. The properties of the graphene oxide-polydimethylsiloxane coating were characterized by transmission electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…Notably, our approach yields low LOD and LOQ values. Other studies that applied CNMs for pesticide analyses using SPME processes have reported detection or quantifcation limits similar to those presented above [44], even with a green coating (cork) [45]. Moreover, the results were better than [46] or similar to [47] using other extraction techniques.…”
Section: Methods Evaluationsupporting
confidence: 70%
“…Notably, our approach yields low LOD and LOQ values. Other studies that applied CNMs for pesticide analyses using SPME processes have reported detection or quantifcation limits similar to those presented above [44], even with a green coating (cork) [45]. Moreover, the results were better than [46] or similar to [47] using other extraction techniques.…”
Section: Methods Evaluationsupporting
confidence: 70%
“…However, these detection methods suffer greatly from matrix interferences within the complex sample matrix, often resulting in false positives . Currently, SPE of nitrogen‐containing heterocyclic fungicides is challenging due to the low adsorption capacity, slow mass transfer, and challenging separation of available adsorbents . Consequently, it is therefore essential to explore inexpensive adsorbents with high, selective adsorption capacities, and high achievable separation for the concentration and treatment of nitrogen‐containing heterocyclic fungicides prior to detection .…”
Section: Introductionmentioning
confidence: 99%
“…A preconcentration step prior to chromatographic analysis is usually needed to decrease the matrix effect and enrich the analytes. Traditional fungicide extraction methods were performed by complicated and solvent‐consuming procedures such as liquid‐phase extraction and SPE, which have been replaced by more environment‐friendly microextraction methods including solid‐phase microextraction (SPME), magnetic solid‐phase extraction, and liquid‐liquid microextraction.…”
Section: Introductionmentioning
confidence: 99%